Morphological functional and psychological indicators of 11-12 yrs age boys' (members of preparatory special health groups of urban and countryside schools) development - G.V. Tamozhanskaya (H.S. Skovoroda Kharkov National Pedagogical University, 2015)
Purpose: determination of anthropometrical and somatic indicators and factors of school anxiety of 11-12 yrs age boys - members of special health groups at urban and countryside schools. Material: in researches 50 boys of 11-12 years age participated. Results: the author determined difference between morphological-functional indicators and kinds of boys' diseases. Besides, attendance of physical culture classes in respect to other subjects was analyzed. Comparative factors of children's school anxiety were outlined. Schoolboys from countryside are more anxious about opinion of peers about themselves. Conclusions: boys' morphological-functional indicators shall be considered as factor of determination and revelation of defects in harmonious development in system of physical education. Attention should be paid to different kinds of diseases and anxiety among boys of preparatory group.